Pengaruh Diversitas Gender Terhadap Sustaianble Awareness Siswa SMK: The Influence of Gender Diversity on Sustainable Awareness of Vocational School Students - Siskawati, Dyah; Khoiri, Nur; Hayat, Muhammad Syaipul (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This article aims to analyze the influence of gender diversity on vocational high school students' sustainability awareness. In this era of globalization and rapid development, it is important for students to have a high awareness of sustainable issues, including in the context of gender. This research involved a sample of Vocational High School students from various gender backgrounds, with the aim of understanding whether gender diversity contributes to increasing students' sustainable awareness.